The Relationship between Entrepreneurial Orientation and Business Performance: Exploring the Moderating Role of Supply Chain Management in SME Sector of Iraq - Miri habeeb, Liqaa; Abd aii ghali, Batool; Hasan kadhim alharguse, Thaer (International Journal of Supply Chain Management, 2019)
The primary objective of this paper is to examine and explore the relationship between Entrepreneurial Orientation and Business Performance in small and medium size enterprises (SMEs) with the moderating role of supply chain management style. The role and importance of SMEs in the overall economic development and employment generation has been an area of great interest for researchers and policy makers. The data was analyzed using structural equation modeling (SEM). It is noted that a positive relationship among Entrepreneurial Orientation and Business Performance is persisting. Furthermore, supply chain management plays an important moderating role in this framework. This study focus on SMEs working in Iraq and provides guidelines for policy makers to consider the importance of supply chain management development for SMEs performance.